2018
DOI: 10.1242/jcs.204065
|View full text |Cite
|
Sign up to set email alerts
|

Paracrine brassinosteroid signaling at the stem cell niche controls cellular regeneration

Abstract: Stem cell regeneration is crucial for both cell turnover and tissue healing in multicellular organisms. In Arabidopsis roots, a reduced group of cells known as the quiescent center (QC) act as a cell reservoir for surrounding stem cells during both normal growth and in response to external damage. Although cells of the QC have a very low mitotic activity, plant hormones such as brassinosteroids (BRs) can promote QC divisions. Here, we used a tissue-specific strategy to investigate the spatial signaling require… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 57 publications
1
33
0
Order By: Relevance
“…We found that cyclin genes, specifically CYCD3;1 and CYCP4;1, are induced by BL and repressed by BRON, suggesting that BR induces these cyclins through its repression of BRON ( Fig 5C). These results are supported by multiple studies which elucidate the role of CYCD3;1 in BR-induced cell division (14,19) and describe how BR specifically induces QC division in the root (14,30,53…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…We found that cyclin genes, specifically CYCD3;1 and CYCP4;1, are induced by BL and repressed by BRON, suggesting that BR induces these cyclins through its repression of BRON ( Fig 5C). These results are supported by multiple studies which elucidate the role of CYCD3;1 in BR-induced cell division (14,19) and describe how BR specifically induces QC division in the root (14,30,53…”
Section: Discussionsupporting
confidence: 55%
“…We found that anl2 mutant roots shorten more than WT when treated with BL, demonstrating that the anl2 mutants are hypersensitive to BL (Fig S4, Table S2). It has also been shown that BL can induce excessive QC divisions in the root (14,30,53). Thus, we checked the anl2 mutant roots for QC divisions as a secondary BR response phenotype: however, we found that anl2 mutant roots do not display excessive QC divisions ( Fig S4).…”
Section: R a F Tmentioning
confidence: 88%
“…We suggest that this is accomplished through the transcriptional control of metabolic pathways that produce osmoprotectant metabolites that accumulate in the roots. While spatial BR signaling has been shown to contribute to stem cell replenishment in response to genotoxic stress 31 , 34 , here we show that ectopic expression of vascular-enriched BRL3 receptors can promote growth during drought. Altogether, our results suggest that spatial regulation of BR signaling can affect plant stress responses.…”
Section: Discussionmentioning
confidence: 53%
“…Recently, greater attention is being placed on the spatial regulation of hormonal signaling pathways in attempt to further understand the coordination of plant growth and stress responses 26 , 31 34 . For instance, while the BRI1 receptor is widely localized in many tissues 35 , the BRI1-LIKE receptor homologs BRL1 and BRL3 signal from the innermost tissues of the plant and thereby contribute to vascular development 12 , 33 , 36 .…”
Section: Introductionmentioning
confidence: 99%
“…The QC prevents differentiation of the surrounding stem cells (van den Berg et al, 1997), and its low proliferation rate provides a way to preserve the genome from replication errors. It also acts as a root stem cells reservoir, having the ability of promoting its own division rate to replenish the stem cells when they are damaged (Fulcher & Sablowski, 2009;Lozano-Elena et al, 2018).…”
Section: Introductionmentioning
confidence: 99%